Akidah Akhlak Teacher’s Strategy in Forming Students’ Responsible Attitude - Uswatun Hasanah; Sulistia Ningrum (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper examines the strategies, obstacles, and solutions employed by Akidah Akhlak teachers in shaping students’ responsible attitudes. The study uses a qualitative approach with data collected through interviews, observations, and documentation. The findings show that teachers apply several strategies, including the use of rewards and punishments, motivational efforts, and personal approaches to students. Obstacles in forming responsible attitudes arise from students’ individual personalities, lack of parental support, and negative peer influences. To address these challenges, teachers implement solutions such as strengthening cooperation with parents, building intensive communication, fostering positive thinking, and providing supportive guidance when assigning tasks. The study contributes to a deeper understanding of the teacher’s role in cultivating students’ responsibility and emphasizes the crucial involvement of parents in supporting the development of responsible attitudes in students.